Perencanaan pengembangan lanskap Jalan Teuku Umar Barat, Kota Denpasar, Bali - Anjelika, Aisyah Dian; Utami, Ni Wayan Febriana; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol.7, No.1, April 2021, 2021)
Teuku Umar Barat street is a collector type of street located in Denpasar City, Bali. High level activities in Teuku Umar Barat street without being accompanied by a good division of space will resulting inconvenience for users. It is also aggravated by the absence of structure and procurement of street facilities. Hence, it needs to be planned to achieve the main function of Teuku Umar Barat street. This study aims to identify the existing condition of Teuku Umar Barat street and to plan it by implementing sustainable streetscape approach. The method used in this research was field survey by conducting observation, interview, and literature study. There were four stages conducting in this research i.e. inventory, analysis, synthesis, and planning. The result of this study showed that the planning applied was natural and cultural resource approach. The sustainable streetscape resulted was planned to provide an optimal balance between community and commercial interests by ensuring the continuity of its existence.